2010
DOI: 10.1039/c002609c
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular hydrogels inspired by collagen for tissue engineering

Abstract: Supramolecular hydrogels are promising biomaterials for cell culture in 2-D and 3-D environments. Inspired by the chemical structure of collagen, which bears the repeating tripeptide of glycine-Xaa-4R-hydroxyproline (GXO; Xaa is any one of the natural amino acids), we designed and synthesized a small library of supramolecular hydrogelators (a total of 6). We found that four of the hydrogels were suitable for NIH 3T3 cell culture in the 2-D environments. Gel 2, the best hydrogel, has properties that are similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…As shown in Figure 3B, solution of gel I exhibited two distinctive peaks at 332 and 339 nm, which corresponded to the 1 L b transition of naphthalene. 35 These peaks showed red shifts in gel I to 335 and 343 nm, respectively. The three small peaks centered at 432, 458 and 483 nm were from the oligomer of naphthalene groups, which suggested that most of naphthalene groups on 1 were separated by other groups in the self-assembled stage.…”
Section: Scheme 1 Chemical Structures Of the Peptides Inspired By Elamentioning
confidence: 97%
See 2 more Smart Citations
“…As shown in Figure 3B, solution of gel I exhibited two distinctive peaks at 332 and 339 nm, which corresponded to the 1 L b transition of naphthalene. 35 These peaks showed red shifts in gel I to 335 and 343 nm, respectively. The three small peaks centered at 432, 458 and 483 nm were from the oligomer of naphthalene groups, which suggested that most of naphthalene groups on 1 were separated by other groups in the self-assembled stage.…”
Section: Scheme 1 Chemical Structures Of the Peptides Inspired By Elamentioning
confidence: 97%
“…[34][35][36][37][38] We recently found that a tetra-peptide derivative of Nap-GFFpY-OMe (Nap represented naphthalene acetic acid, G represented glycine, F represented phenylalanine, pY represented phosphorylated tyrosine, and OMe represented methyl ester) could form hydrogels at a minimum gelation concentration of 0.01 wt% after enzymatic conversion. 34 This was the most efficient gelator reported up to now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also suggested that the hydrogel of 60 is the best hydrogel having properties that are similar to those of collagen for 3T3 cell culture. [111] Using the similar approach to generate a supramolecular hydrogelator that has a longer collagen mimic sequence, they demonstrated that its corresponding supramolecular hydrogel supported the differentiation of murine ES cells. [112] These findings illustrate the effectiveness of aromatic-aromatic interactions for generating supramolecular hydrogel scaffolds that mimic nature for tissue engineering.…”
Section: Supramolecular Hydrogels Made Of Aminoacidsmentioning
confidence: 99%
“…As one of recently most investigated areas of materials research, supramolecular hydrogels has been developed into promising biomaterials for drug delivery, [1][2][3][4][5][6] tissue engineering, [7][8][9][10][11][12] etc. due to their easily obtained biocompatibility and biodegradability that resulted from non-covalent aggregation and self-assembly of the hydrogelators.…”
Section: Introductionmentioning
confidence: 99%